2006
DOI: 10.1021/jp061975u
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Study of the Interfacial Electron Transfer Pathway for Monolayer-Adsorbed InN on the TiO2 Anatase (101) Surface

Abstract: Density functional theory (DFT) in connection with ultrasoft pseudopotential (USP) and generalized gradient spin-polarized approximations (GGSA) is applied to calculate the adsorption energies and structures of monolayer-adsorbed InN on the TiO(2) anatase (101) surface and the corresponding electronic properties, that is, partial density of states (PDOS) for surface and bulk layers of the TiO(2) anatase (101) surface and monolayer-adsorbed InN, to shed light on the possible structural modes for initial photoex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 21 publications
(24 reference statements)
0
11
0
Order By: Relevance
“…Similarly on the T101 surface (Figure b), the band at 3033 cm –1 corresponding to C–H stretching vibrations of the aromatic ring, the bands at 2929, 2917, 2909, 2853, and 2842 cm –1 corresponding to asymmetric and symmetric C–H stretching vibrations of the methyl group, and the band at 1436 cm –1 corresponding to methyl bending vibration also appear after introduction of toluene. It should be pointed out that the positions of these characteristic bands of adsorbed toluene on T101 are red-shifted slightly compared to that on T001, which may be attributed to the different Ti 4+ adsorption sites on {001} and {101} facets for toluene adsorption. , Notably, the adsorption takes much longer for T101 to reach a stable level. For easy understanding, the integrated areas of the characteristic bands of C–H stretching vibrations of toluene on T001 and T101 facets as a function of adsorption time are shown in Figure .…”
Section: Results and Discussionmentioning
confidence: 97%
“…Similarly on the T101 surface (Figure b), the band at 3033 cm –1 corresponding to C–H stretching vibrations of the aromatic ring, the bands at 2929, 2917, 2909, 2853, and 2842 cm –1 corresponding to asymmetric and symmetric C–H stretching vibrations of the methyl group, and the band at 1436 cm –1 corresponding to methyl bending vibration also appear after introduction of toluene. It should be pointed out that the positions of these characteristic bands of adsorbed toluene on T101 are red-shifted slightly compared to that on T001, which may be attributed to the different Ti 4+ adsorption sites on {001} and {101} facets for toluene adsorption. , Notably, the adsorption takes much longer for T101 to reach a stable level. For easy understanding, the integrated areas of the characteristic bands of C–H stretching vibrations of toluene on T001 and T101 facets as a function of adsorption time are shown in Figure .…”
Section: Results and Discussionmentioning
confidence: 97%
“…The DOS indicated that states are basically absence of spin polarization but the states on fermi level are spin‐polarized to some extent. The contribution of iodide states near fermi level points to the feasibility of charge transfer from the host slab to the adsorbent [26].…”
Section: Resultsmentioning
confidence: 99%
“…Experimental [1] and theoretical [2] literature suggest that the light harvesting component of the anatase based dye-sensitized solar cell (DSSC), typically a Ru-based dye molecule, could be replaced by a monolayer of InN. In [1], a "monolayer" of InN was deposited via chemical vapor deposition on a nanoparticulate anatase TiO 2 substrate.…”
Section: Introductionmentioning
confidence: 99%
“…In [1], a "monolayer" of InN was deposited via chemical vapor deposition on a nanoparticulate anatase TiO 2 substrate. Calculations [2] indicate that electrons from InN would be excited over a 1.7 eV band gap into the conduction band, from whence the electrons would be injected from the InN conduction band into the TiO2 conduction band via band gap overlap. Calculations [2] indicate that electrons from InN would be excited over a 1.7 eV band gap into the conduction band, from whence the electrons would be injected from the InN conduction band into the TiO2 conduction band via band gap overlap.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation